Social network analysis and co-occurrence : identifying the gaps - Dörpinghaus, Jens [Verfasser] (My University, 2022)
"Social Network Analysis is widely used in the humanities. However, historical and narrative texts in ancient languages are usually challenging for NLP (natural language processing) methods and AI (artificial intelligence) technologies developed for modern languages due to their complexity and missing models. In this article, we will focus on biblical texts. Here, linguistic resources are already available. However, no approaches for the automated linking of actors and other information, e.g. spatiality, are available. Thus, in this paper, we will analyze if co-occurrence might improve the linking of data in manual exegetical work. We will provide a detailed analysis and evaluation to identify the gaps for further research. The results of this paper are not limited to theology, but can be applied in all fields working with textual information." (Authors' abstract, BIBB-Doku)
Keywords: 370; Soziales Netzwerk; Netzwerkanalyse; Textanalyse